2018
DOI: 10.1002/jez.2174
|View full text |Cite
|
Sign up to set email alerts
|

Cavities shield birds from effects of artificial light at night on sleep

Abstract: Light pollution is an ever increasing worldwide problem disrupting animal behavior. Artificial light at night (ALAN) has been shown to affect sleep in wild birds. Even cavity-nesting bird species may be affected when sleeping inside their cavity. Correlational studies suggest that light from outside the cavity/nest box, for example from street lights, may affect sleep. We used an experimental design to study to what extent nest boxes shield animals from effects of ALAN on sleep. We recorded individual sleep be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…2017 ). Alternatively, the immediate rearing environment of the nestlings, i.e., the enclosed nest-box, could have buffered the exposure of certain types of urban stressors, such as artificial light at night ( Raap et al. 2018 ), such that urbanization effects on AOX are not readily observed before fledging.…”
Section: Discussionmentioning
confidence: 99%
“…2017 ). Alternatively, the immediate rearing environment of the nestlings, i.e., the enclosed nest-box, could have buffered the exposure of certain types of urban stressors, such as artificial light at night ( Raap et al. 2018 ), such that urbanization effects on AOX are not readily observed before fledging.…”
Section: Discussionmentioning
confidence: 99%
“…Dominoni et al (2018) assessed dose-dependent responses of the reproductive system. Raap, Pinxten, and Eens (2018) asked whether roosting in cavities may limit the effects of light pollution on sleep. Other passerine bird species included in this issue are the Indian Weaver Bird (Ploceus philippinus) and the Zebra finch ( Taeniopygia guttata ).…”
Section: The Effects Of Alan On Different Speciesmentioning
confidence: 99%
“…Finally, several studies showed that exposure to artificial night lighting influences activity patterns and sleep (e.g. Kempenaers et al 2010, Dominoni et al 2013, 2014, Russ et al 2015, Raap et al 2016, Sun et al 2017; but see Raap et al 2018).…”
mentioning
confidence: 99%